The impact of hypertension education on self-care management in hypertensive patients in Senderak village health centre - Silvia Nora Anggreini; Faridah Mohd Said; Awaliyah Ulfah Ayudytha Ezdha; Dwi Elka Filri; Fitra Wahyuni; Isna Ovari (Journal of the Pakistan Medical Association, 2024)
Objective:To determine the effect of hypertension education on self-care management in hypertensive patients in a rural setting. Method:The quasi-experimental study was conducted in January and February 2022 at the Senderak Village Health Centre, Bengkalis, Indonesia, and comprised hypertension patients without any complications referred to the community health centre between August 2021 and January 2022. The subjects underwent self-care education intervention. The knowledge level was assessed at baseline and post-intervention using the Hypertension Self-Management Behaviour Questionnaire. Data was analysed using IBM SPSS Statistic v23 software. Results: All the 30(100%) patients were females, 12(40%) were aged 46-55 years, 20(66.7%) had received elementary school education and 25(83.3%) were housewives. There were 21(70%) respondents with stage II hypertension having systolic blood pressure greater than or equal to 160mmHg. The mean level of knowledge about self-care management of hypertension increased significantly post-intervention (p<0.0001). Conclusion: Health education could improve knowledge on self-care management of hypertension in hypertensive patients. Keywords: Blood Pressure, Self Care, Hypertension, Kidney, Brain.